Macrophage density is an adverse prognosticator for ipsilateral recurrence in ductal carcinoma in situ. (August 2022) - Darvishian, Farbod; Wu, Yinxiang; Ozerdem, Ugur; Chun, Jennifer; Adams, Sylvia; Guth, Amber; Axelrod, Deborah; Shapiro, Richard; Troxel, Andrea B.; Schnabel, Freya; Roses, Daniel
Abstract: Introduction: There is evidence that supports the association of dense tumor infiltrating lymphocyte (TILs) with an increased risk of ipsilateral recurrence in ductal carcinoma in situ (DCIS). However, the association of cellular composition of DCIS immune microenvironment with the histopathologic parameters and outcome is not well understood. Methods: We queried our institutional database for patients with pure DCIS diagnosed between 2010 and 2019. Immunohistochemical studies for CD8, CD4, CD68, CD163, and FOXP3 were performed and evaluated in the DCIS microenvironment using tissue microarrays. Statistical methods included Fisher's exact test for categorical variables and the two-sample t -test or the Wilcoxon Rank-Sum test for continuous variables. Results: The analytic sample included 67 patients. Median age was 62 years (range = 53 to 66) and median follow up was 6.7 years (range = 5.3 to 7.8). Thirteen patients had ipsilateral recurrence. Of all the clinicopathologic variables, only the DCIS size and TIL density were significantly associated with recurrence (p = 0.023 and 0.006, respectively). After adjusting for age and TIL density, only high CD68 (>50) and high CD68/CD163 ratio (>0.46) correlated with ipsilateral recurrence (p = 0.026 and 0.013, respectively) and shorter time to recurrence [hazard ratio 4.87 (95% CI: 1.24–19, p = 0.023) and 10.32 (95% CI: 1.34–80, p = 0.025), respectively]. Conclusions: In addition to DCIS size and TIL density, high CD68 + tumor-associated macrophages predict ipsilateral recurrence in DCIS. High CD68 + macrophage density and CD68/CD163 ratio also predict a shorter time to recurrence. Highlights: Tumor associated macrophages predict recurrence in ductal carcinoma in situ. High macrophage density predicts less time to ductal carcinoma in situ recurrence. Carcinoma size and tumor infiltrating lymphocyte density associated with recurrence.